Odysseys Home : Mapping African-Canadian Literature - Clarke, George Elliott (Toronto : University of Toronto Press, 2017)
Odysseys Home: Mapping African-Canadian Literatureis a pioneering study of African-Canadian literary creativity, laying the groundwork for future scholarly work in the field. Based on extensive excavations of archives and texts, this challenging passage through twelve essays presents a history of the literature and examines its debt to, and synthesis with, oral cultures. George Elliott Clarke identifies African-Canadian literature's distinguishing characteristics, argues for its relevance to both African Diasporic Black and Canadian Studies, and critiques several of its key creators and texts. Scholarly and sophisticated, the survey cites and interprets the works of several major African-Canadian writers, including André Alexis, Dionne Brand, Austin Clarke, Claire Harris, and M. Nourbese Philip. In so doing, Clarke demonstrates that African-Canadian writers and critics explore the tensions that exist between notions of universalism and black nationalism, liberalism and conservatism. These tensions are revealed in the literature in what Clarke argues to be -paradoxically -uniquely Canadianandproudly apart from a mainstream national identity. Clarke has unearthed vital but previously unconsidered authors, and charted the relationship between African-Canadian literature and that of Africa, African America, and the Caribbean. In addition to the essays, Clarke has assembled a seminal and expansive bibliography of texts -literature and criticism -from both English and French Canada. This important resource will inevitably challenge and change future academic consideration of African-Canadian literature and its place in the international literary map of the African Diaspora.
Frontmatter -- Contents -- Acknowledgments -- A Note on the Text -- Embarkation: Discovering African-Canadian Literature -- PART ONE. SORTIES -- Contesting a Model Blackness: A Meditation on African-Canadian African-Americanism, or the Structures of African-Canadianite -- Must All Blackness Be American? Locating Canada in Borden's 'Tightrope Time' or Nationalizing Gilroy's The Black Atlantic -- The Career of Black English in Nova Scotia: A Literary Sketch -- The Birth and Rebirth of Africadian Literature -- Syl Cheney-Coker's Nova Scotia, or the Limits of Pan-Africanism -- Toward a Conservative Modernity: Cultural Nationalism in Contemporary Acadian and Africadian Poetry -- Liberalism and Its Discontents: Reading Black and White in Contemporary Quebecois Texts -- Treason of the Black Intellectuals? -- Canadian Biraciality and Its 'Zebra' Poetics -- Clarke versus Clarke: Tory Elitism in Austin Clarke's Short Fiction -- Harris, Philip, Brand: Three Authors in Search of Literate Criticism -- No Language Is Neutral: Seizing English for Ourselves -- PART TWO. INCURSIONS: SELECTED REVIEWS -- The Complex Face of Black Canada -- Viewing African Canada -- The Death and Rebirth ofAfricadian Nationalism -- An Unprejudiced View of Two Africadian Poets -- Reading Ward's 'Blind Man's Blues' -- African-Islanders -- Another Great Thing -- Growing Up Black in Alberta -- Toward a Black Women's Canadian History -- Love Which Is Insight -- The Outraged Citizen-Poet Speaks Out -- PART THREE. SURVEYS -- A Primer of African-Canadian Literature -- Africana Canadiana: A Select Bibliography of Literature by African-Canadian Authors, 1785-2001, in English, French, and Translation -- Works Cited -- Index.
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 13. Sep 2017).
eBooks on EBSCOhost
Keywords: Africans -- Canada -- Intellectual life; Canadian literature -- Black authors -- Bibliography; Canadian literature -- Black authors -- History and criticism; French-Canadian literature -- Black authors -- History and criticism; Africains -- Canada -- Vie intellectuelle; Littérature canadienne-française -- Auteurs noirs -- Histoire et critique; LITERARY CRITICISM -- American -- General; Africans -- Intellectual life; Canadian literature -- Black authors; Canada; Bibliographies; Criticism, interpretation, etc